(untitled) (Research, Society and Development, 2025)
The present study aims to identify the possible effects of soy isoflavone in migraine therapy in adult patients. To understand the state of the art on the topic, we opted for a bibliographical survey, however, as there was a lack of work, a narrative review was carried out without a time frame, using the PubMed, Medline and LILACS databases, in addition to searching through Google Scholar, using the association between the descriptors “Isoflavonas”, “Isoflavones”, “Soy isoflavone”, “Enxaqueca”, “Migraine”, “Migraine disorders”, including only studies in Portuguese, English and Spanish, with full texts available and which address the effects of isoflavones on migraines and their impacts on the health of adults. Only two epidemiological studies were found that investigated the direct association between the consumption of soy isoflavones and the repercussions on the symptoms of the disease. The other results were from articles that cited isoflavone as one of the food components with potential benefit for the clinical condition caused by migraine and its consequences on the patient’s quality of life. Furthermore, an association was made between these effects promoted by isoflavone in the body and its usefulness in some mechanisms related to migraine. The scarcity of studies on the direct relationship between isoflavone consumption and its action on migraine symptoms made it difficult to write this work robustly, but also reinforced the novelty of this topic, worthy of further studies.